Visualization by Live-Cell Microscopy of Disruption of ND10 during Herpes Simplex Virus Type 1 Infection - Everett, Roger D. (American Society for Microbiology, 2004)
ND10 structures are disrupted during herpes simplex virus type 1 (HSV-1) infection by viral regulatory protein ICP0. The significance of this effect remains controversial, partly because of a report that high-level expression of the major ND10 promyelocytic leukemia (PML) protein precludes ND10 disruption yet does not inhibit HSV-1 infection. Here we demonstrate dramatic reorganization of ND10 during HSV-1 infection by live-cell microscopy, even in the presence of overexpressed PML.